Coercion in psychiatric and mental health nursing: A conceptual analysis. (10th March 2021) - Paradis‐Gagné, Etienne; Pariseau‐Legault, Pierre; Goulet, Marie‐Hélène; Jacob, Jean Daniel; Lessard‐Deschênes, Clara
Abstract: The use of coercion in psychiatric and mental health nursing is a major challenge, which can lead to negative consequences for nurses and patients, including rupture in the therapeutic relationship and risk of injury and trauma. The concept of coercion is complex to define and is used in different ways throughout the nursing literature. This concept is defined broadly, referring to both formal (seclusion, restraint, and forced hospitalization), informal (persuasion, threat, and inducement), and perceived coercion, without fully addressing its evolving conceptualizations and use in nursing practice. We conducted a concept analysis of coercion using Rodgers' evolutionary method to identify its antecedents, attributes, and associated consequences. We identified five main attributes of the concept: different forms of coercion; the contexts in which coercion is exercised; nurses' justification of its use; the ethical issues raised by the presence of coercion; and power dynamics. Our conceptual analysis shows the need for more nursing research in the field of coercion to achieve a better understanding of the power dynamics and ethical issues that arise in the presence of coercion.